2014
DOI: 10.1016/j.phytochem.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Asphodosides A-E, anti-MRSA metabolites from Asphodelus microcarpus

Abstract: Bioassay guided fractionation of the ethanolic extract of Asphodelus microcarpus Salzm. et Viv. (Xanthorrhoeaceae or Asphodelaceae) resulted in isolation of five compounds identified as asphodosides A-E (1–5). Compounds 2–4 showed activity against methicillin resistant Staphylococcus aureus (MRSA) with IC50 values of 1.62, 7.0 and 9.0 μg/mL, respectively. They also exhibited activity against Staphylococcus aureus (non-MRSA) with IC50 values of 1.0, 3.4 and 2.2 μg/mL, respectively. The structure elucidation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
1
16
0
1
Order By: Relevance
“…Various biological activities have been reported for A. microcarpus , [12, 13]. Phytochemical studies on A. microcarpus revealed the presence of lipids, carbohydrates, sterols, anthraquinones and arylcoumarins [13, 14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various biological activities have been reported for A. microcarpus , [12, 13]. Phytochemical studies on A. microcarpus revealed the presence of lipids, carbohydrates, sterols, anthraquinones and arylcoumarins [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Various biological activities have been reported for A. microcarpus , [12, 13]. Phytochemical studies on A. microcarpus revealed the presence of lipids, carbohydrates, sterols, anthraquinones and arylcoumarins [13, 14]. It is well known that the last two compounds have tyrosinase inhibitory activity [1517] and plant extracts with antimelanogenic activity typically possess polyphenols such as flavonoids, which are usually the factors responsible for the activities in plant extracts [18].…”
Section: Introductionmentioning
confidence: 99%
“…The ethanol extracts of leaves demonstrated strong antiviral activity against Ebola virus (EBOV) in the concentration of 0.1–0.3 µg/mL [49]. Although the leaf seems to have stronger antimicrobial activity in comparison with roots, in general, both exhibit weak or no antimicrobial/antifungal activity [20,48,49,70]; however, compounds isolated from root tubers extracts showed potent activity such as asphodelin A against S. aureus (MIC = 16 µg/mL), Escherichia coli (MIC = 4 µg/mL), Pseudomonas aeruginosa (MIC = 8 µg/mL), Candida albicans (MIC = 64 µg/mL) [19] and Botrytis cinerea (MIC = 128 µg/mL) and asphodoside B against MRSA (IC 50 = 1.62 μg/mL) [51]. Other isolated compounds from root extracts showed different biological activity; for instance, ramosin showed potent cytotoxic activity against leukemia cell lines [21], aestivin showed potent antimalarial activity against chloroquine-sensitive and resistant strains of Plasmodium falciparum with IC 50 of 0.8–0.7 μg/mL [21] and 3,4-dihydroxy-methyl benzoate exhibited anti-parasitic activity against Leishmania donovani promastigotes with IC 50 of 33.2 µg/mL [54].…”
Section: Resultsmentioning
confidence: 99%
“…[28] Anthraquinones Anthraquinones are a class of natural compounds that consist of several hundred compounds that differ in the nature .0 and 9.0 μg/mL, respectively. [29] Emodin (53), purified from the extract of Hypericum riparium leaves also showed significant antimicrobial potential (IC50 = 11.71 μg/mL) against MRSA. Further research revealed that compound 53 could damage the integrity of cell wall, leading to loss of intracellular components ( Figure 5).…”
Section: Coumarinsmentioning
confidence: 99%